Crime survey for England and Wales, 2017-2018: teaching dataset (UK Data Service, 2020)
This teaching dataset is based on the Crime Survey for England and Wales, 2017-2018 (CSEW) (held by the UK Data Service under SN 8464). It contains data for all 34,715 cases from the CSEW 2017-2018 (adult non-victim form dataset) for a selection of variables.